Synthesis of Ionophore from p-t-Butyl-(carboxymethoxy)calix[4]arene Substituted Amide - Nasriadi Dali; Seniwati Dali; Armadi Chairunnas; Hilda Ayu Melvi Amalia; Sri Ayu Andini Puspitasari (Molekul, 2023)
The ionophore has been successfully synthesized from p-t-butyl(carboxymethoxy)calix[4]arene subtituted amide. The ionophore was obtained in two steps of the synthesis reaction. The first step is the chlorination reaction of p-t-butyl(carboxymethoxy)calix[4]arene with thionyl chloride in dry benzene solvent. The product of the chlorination reaction is p-t-butyl(chloroacetylmethoxy)calix[4]arene in the form of the light brown viscous liquid with the rendemen of 78.25% and TLC (SiO2, CH3OH : CH2Cl2 = 1 : 1 v/v, Rf = 0.65). The second step is the amidation reaction of p-t-butyl(chloroacetylmethoxy) calix[4]arene with dimethylamine in dry tetrahydrofuran solvent. The product of the amidation reaction is p-t-butyl(dimethylcarbamoylmethoxy)-calix[4]arene or the DIMECAC4ND3 ionophore in the form of white solid with the rendemen of 60.75%, a melting point of 277-279 °C, and TLC (SiO2, CH3OH : CH2Cl2 = 1 : 1 v/v, Rf = 0.82).